2015
DOI: 10.1080/23723556.2014.999513
|View full text |Cite
|
Sign up to set email alerts
|

Taspase 1: A protease with many biological surprises

Abstract: Taspase 1 (TASP1) cleaves the mixed-lineage leukemia (MLL) and transcription factor (TF) IIA families of nuclear proteins to orchestrate various biological processes. TASP1 is not a classical oncogene, but assists in cell proliferation and permits oncogenic initiation through cleavage of MLL and TFIIA. TASP1 is thus better classified as a “non-oncogene addiction” protease, and targeting TASP1 offers a novel and attractive anticancer therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 10 publications
1
31
0
2
Order By: Relevance
“…TASP1 is classified as a "non-oncogene addiction" protease and plays an important role in various cancer development [20,23]. Herein, we for the first time found that TASP1 is highly expressed in GBC tissues compared with the matched non-malignant tissues.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…TASP1 is classified as a "non-oncogene addiction" protease and plays an important role in various cancer development [20,23]. Herein, we for the first time found that TASP1 is highly expressed in GBC tissues compared with the matched non-malignant tissues.…”
Section: Discussionmentioning
confidence: 83%
“…Taspase 1 (threonine aspartase 1; TASP1) was initially identified as an endopeptidase responsible for cleaving mixed lineage leukemia 1 (MLL1) protein for proper regulation of HOX expression [20,21]. Other genetically and biochemically proven TASP1 substrates include MLL2, TFIIAα-β, ALFα-β, and Drosophila HCF-1 [22][23][24]. Interestingly, all of these substrates are broad-acting nuclear factors that regulate gene expression, suggesting a critical role for TASP1 in the orchestration of various biological processes [23].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…The proteolytic cleavage activation of GTFIIA is essential for male spermatogenesis, craniofacial development, and maintenance of fetal liver hematopoietic stem cells. 10 The role of taspase 1 is further supported by studying taspase 1 −/− mice model which showed early postnatal lethality, skeletal abnormalities, and in utero and postnatal growth failure. 11 Although this phenotype seems to be more severe than that of the infant described here, the vital role (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Taspase is a conserved threonine-aspartic acid protease that cleaves mammalian and Drosophila MLL1/trithorax, as well as other nuclear proteins ( e.g. , TFIIA) associated with chromatin and transcription; mutations in human Taspase1 have been associated with certain forms of cancer, particularly those of the head and neck ( Hsieh et al 2003a ; Hsieh et al 2003b ; Khan et al 2005 ; Takeda et al 2006 ; Zhou et al 2006 ; Oyama et al 2013 ; Niizuma et al 2015 ; Takeda et al 2015 ; Stauber et al 2016 ; Gribko et al 2017 ). The four independent mutations are placed on the tasp-1 genomic locus as shown in Figure 5A .…”
Section: Resultsmentioning
confidence: 99%